Management of Tahfidz Program and Its Role in Character Building for Generation Alpha Students at MI Leuwiliang - Makarim, Helwiyah; Anna Ratnasari; Abellia Nitis Aisya (Jurnal Pendidikan Kreatif, 2026)
This study investigates the influence of tahfidz program management on the character education of Generation Alpha students at Madrasah Ibtidaiyah Muhammadiyah Leuwiliang. The research is motivated by the increasing urgency of character development in the digital era, where Generation Alpha grows up in a technology-saturated environment and faces increasingly complex moral challenges. The tahfidz program is regarded as an effective Islamic educational approach to instill character values through structured and systematic management. A quantitative descriptive approach was employed. The population consisted of 346 students from grades IV, V, and VI, with a sample of 35 students selected using Slovin’s formula. Data were collected through a questionnaire based on management indicators (planning, organizing, actuating, and controlling) and character education indicators. The data were analyzed using simple linear regression and a t-test. The findings indicate that the tahfidz program was implemented effectively, and students demonstrated positive character traits, particularly in religiosity, discipline, and responsibility. Regression analysis confirmed a significant effect influence of tahfidz program management on character education, with a significance value of 0.047 and a coefficient of determination (R²) of 0.2281. This suggests that the management of the tahfidz program contributes 22.81% to the development of students’ character. These findings highlight the importance of structured tahfidz program management in fostering moral resilience among Generation Alpha.